Physical and shielding protection parameterization of PbOZnO- B₂O₃-SiO₂ glass network - Razali, Nur Ain Nabilah; Mustafa, Iskandar Shahrim; Noor Azman, Nurul Zahirah; Mohamed Kamari, Halimah; Mat Hashim, Intan Sofea; Ahmad, Nurulshuhada; Norazam, Nur Afini; Che Asudin, Che Amira Shahira (IOP Publishing, 2018)
Glass series of quaternary lead-zinc-borosilicate glass was fabricated using melt-quenching method. It was successfully prepared using silicon dioxide (SiO2 99.37 %) as the network former, which was obtains from rice husk ash (RHA). The thickness of the prepared glass samples used during the measurement was 0.3, 0.4 and 0.5 cm. As the percentage of PbO increased from 5% to 40%, the density and molar volume of glass sample increased from 3.719 g/cm3 to 5.010 g/cm3 and 21.44 cm3 to 25.82 cm3, respectively. The significant modification was due to augmentation in bond length and increment in inter-atomic spacing between atoms with the presence of Pb, Zn and B atoms. Nevertheless, the oxygen packing density decreased from 79.29 g-atom/l to 65.84 g-atom/l. The mass attenuation coefficient was found to be increased for 0.3 cm, 0.4 cm and 0.5 cm. The escalating mass attenuation coefficient was due to the increment of PbO percentage mole, which related to the emergent photoelectric absorption of the glass sample. Thus, it also affects the decreasing trend of Half Value Layer (HVL) and the increasing of Effective atomic number (Zeff).